Analisis Finansial Dan Komposisi Tanaman Dalam Rangka Persiapan Pengajuan Izin Hkm (Studi Kasus Desa Margosari Kecamatan Pagelaran Utara Kabupaten Pringsewu) - Helen Yuseva Ayu; Rommy Qurniati; Rudi Hilmanto (Jurnal Sylva Lestari, 2015)
Social forestry (HKm) is a state forest utilization primarily intended to empower local communities with a purpose sustainable forest and prosperous society. Margosari village currently proposing for HKm the work area permits the Minister of Forestry Republic of Indonesia. One of the requirements to HKm is composition of plants consists of the kind of forest plant, agricultural crops, and crops plantation. To supporting the HKm programs, it is necessary to assess the composition of the plants with in the candidate HKm area of Margosari Village and whether the results from the plant composition is financially suitable and capable of providing prosperity to the farmers of Margosari village. The research was conducted in the Margosari Village of Pagelaran Utara District, Pringsewu Regency in August 2013. Sampling was done using simple random sampling method. Data analysis was conducted using quantitative descriptive analysis method. The results of the showed that the plant composition already fill the HKm criteria is wooden plant more than 200/ha (400/ha) with forest plant species of 28.88%, agricultural crops of 14.63% of agricultural crops and crops plantation of 56.49%. The result from agroforestry HKm based on analysis in a financially Net Present Value (NPV) of Rp 69,088,522.37/ha, Benefit Cost Ratio (BCR) of 1.96 and Internal Rate of Return (IRR) of 29%. However the level of Sajogyo (1997), income from agroforestry HKm don't providing prosperity to the farmers, because can still population with a category near poor of 51.52%. Keywords: social forest, composition of plants, financial analysis, welfare